De-escalated therapy for HR+/HER2+ breast cancer patients with Ki67 response after 2-week letrozole: results of the PerELISA neoadjuvant study. (18th February 2019) - Guarneri, V; Dieci, M V; Bisagni, G; Frassoldati, A; Bianchi, G V; De Salvo, G L; Orvieto, E; Urso, L; Pascual, T; Paré, L; Galván, P; Ambroggi, M; et al.
Abstract: Background: In human epidermal growth factor receptor 2 (HER2+) breast cancers, neoadjuvant trials of chemotherapy plus anti-HER2 treatment consistently showed lower pathologic complete response (pCR) rates in hormone receptor (HR) positive versus negative tumors. The PerELISA study was aimed to evaluate the efficacy of a de-escalated, chemotherapy-free neoadjuvant regimen in HR+/HER2+ breast cancer patients selected on the basis of Ki67 inhibition after 2-week letrozole. Patients and methods: PerELISA is a phase II, multicentric study for postmenopausal patients with HR+/HER2+ operable breast cancer. Patients received 2-week letrozole, and then underwent re-biopsy for Ki67 evaluation. Patients classified as molecular responders (Ki67 relative reduction >20% from baseline) continued letrozole and started trastuzumab-pertuzumab for five cycles. Patients classified as molecular non-responders started weekly paclitaxel for 13 weeks combined with trastuzumab-pertuzumab. Primary aim was breast and axillary pCR. According to a two-stage Simon's design, to reject the null hypothesis, at least 8/43 pCR had to be documented. Results: Sixty-four patients were enrolled, 44 were classified as molecular responders. All these patients completed the assigned treatment with letrozole-trastuzumab-pertuzumab and underwent surgery. A pCR was observed in 9/44 cases (20.5%, 95% confidence interval 11.1% to 34.5%). Among molecular non-responders, 16/17 completed treatment and underwent surgery, with pCR observed in 81.3% of the cases. PAM50 intrinsic subtype was significantly associated with Ki67 response and pCR. Among molecular responders, the pCR rate was significantly higher in HER2-enriched than in other subtypes (45.5% versus 13.8%, P = 0.042). Conclusions: The primary end point of the study was met, by reaching the pre-specified pCRs. In patients selected using Ki67 reduction after short-term letrozole exposure, a meaningful pCR rate can be achieved without chemotherapy. PAM50 intrinsic subtyping further refines our ability to identify a subset of patients for whom chemotherapy might be spared. EUDRACT number: 2013-002662-40 ClinicalTrials.gov Identifier: NCT02411344